Oridonin inhibits the migration and epithelial‐to‐mesenchymal transition of small cell lung cancer cells by suppressing FAK‐ERK1/2 signalling pathway. Issue 8 (13th March 2020) - Xu, Linhao; Bi, Yanli; Xu, Yizhou; Zhang, Zhuocheng; Xu, Wenjie; Zhang, Sisi; Chen, Jian
Abstract: Small cell lung cancer (SCLC) is a severe malignant with high morbidity; however, few effective and secure therapeutic strategy is used in current clinical practice. Oridonin is a small molecule from the traditional Chinese herb Rabdosia rubescens. This study mainly aimed to investigate the role of oridonin on inhibiting the process of H1688, a kind of small cell lung cancer cells from human. Oridonin could suppress H1688 cell proliferation and induce their apoptosis in a high dosage treatment (20 μmol/L). Meanwhile, cell migration was suppressed by oridonin (5 and 10 μmol/L) that did not affect cell proliferation and apoptosis. The expression level of E‐cadherin was significantly increased, and the expression of vimentin, snail and slug was reduced after administration of oridonin. These expression changes were associated with the suppressed integrin β1, phosphorylation of focal adhesion kinase (FAK) and ERK1/2. In addition, oridonin (5 and 10 mg/kg) inhibited tumour growth in a nude mouse model; however, HE staining revealed a certain degree of cytotoxicity in hepatic tissue after treatment oridonin (10 mg/kg). Furthermore, the concentration of alanine aminotransferase (ALP) was significantly increased and lactate dehydrogenase (LDH) was reduced after oridonin treatment (10 mg/kg). Immunohistochemical analysis further revealed that oridonin increased E‐cadherin expression and reduced vimentin and phospho‐FAK levels in vivo. These findings indicated that oridonin can inhibit the migration and epithelial‐to‐mesenchymal transition (EMT) of SCLC cells by suppressing the FAK‐ERK1/2 signalling pathway. Thus, oridonin may be a new drug candidate to offer an effect of anti‐SCLC with relative safety.